PENILAIAN TINGKAT KESEHATAN LEMBAGA PERKREDITAN DESA DI KECAMATAN RENDANG, KABUPATEN KARANGASEM BALI - Ni Made Sudewi Wiadnyani (Universitas Triatma Mulya, 2021)
This study aims to determine the health level of the LPD in the district. Rendang, Kab. Karangasem - Bali seen from the CAMEL system (Capital, Asset Quality, Management, Earning, and Liquidity). LPD in Kec. Rendang totaled 26 LPD for the period 2016 and 2017, but for the 2018 period it decreased to 21 LPD, there were 5 LPDs that were not operational. The criteria for calculating the financial ratios that are said to be healthy are the capital adequacy ratio (CAR) of at least 8%, Akativa Quality (KAP) is 0%, Management (NPM) 0% -100%, Income (ROA) = 1,215%, and Liquidity (LDR). ) a maximum of 94.75%. The research method used in this research is a quantitative research method in the form of financial reports (balance sheet and profit and loss report) for the period 2016 - 2018, as for the data collection methods carried out by interviews, non-behavioral observations, and distributing questionnaires to each LPD. data obtained from .LPLPD Karangasem and LPD in Kec. Rendang. The calculation of the ratios of CAR, KAP, ROA, and LDR is generally considered HEALTHY criteria, but the management measurement ratio (NPM) shows that the results are generally NOT HEALTHY. The results of the questionnaire obtained from the field also showed the lowest average score, for operational management, owner management and management. The results of the analysis can be used as management considerations in making decisions in improving performance and as an assessment of Krama Desa in entrusting financial management.